Perception of the school community regarding educational itineraries in the New High School: difficulties and facilitating factors (Revista de Estudios Teóricos y Epistemológicos en Política Educativa, 2024)
This study aims to analyze the perceptions of students, teachers, and school managers regarding the implementation and selection of educational itineraries in the New High School, restructured by Law no. 13,415/2017, which amended Article 36 of Law no. 9,394/1996, to incorporate itineraries into the school curriculum. The research, conducted on June 21, 2024, involved 75 students, nine teachers, and one school manager from a school in the state of Santa Catarina, Brazil, using a case study as the research method. Data collection was carried out through a structured electronic questionnaire, distributed via an application link. The collected data were analyzed using content analysis. Among the results, a significant age-grade discrepancy was observed, with a mismatch between students’ ages and their respective grade levels. Furthermore, most participants identified the itineraries “Life Project,” “Second Foreign Language,” and “Elective Curriculum Components” as the most common in the school. The study also highlighted the difficulties students faced in choosing their educational itineraries, even with the support from parents, peers, and teachers, revealing a need for greater guidance and support from the educational system.Keywords: Age-grade discrepancy. Educational itineraries. New High School.